Acute appendicitis and rotavirus infection in an infant - R.L. Koehler; R. Phillips; J. Diaz-Miron (Elsevier, 2020)
Appendicitis is the most common surgical disease in the pediatric population, yet most patients are preschool age or older at the time of diagnosis. Rarely, appendicitis does occur in infants. The diagnosis of acute appendicitis in an infant is less commonly considered, given its rarity and often vague presenting symptoms. When the diagnosis is missed in this age group, greater morbidity and mortality may occur. Typically, appendicitis is not associated with gastroenteritis, however, we present a 3-month-old with acute appendicitis with concurrent rotavirus infection.